Self‐concept and health anxiety relate to psychological outcomes for BRCA1/2 carriers. Issue 10 (11th August 2020) - Butler, Ellen; Collier, Sonya; Boland, Michael; Hanhauser, Yvonne; Connolly, Elizabeth; Hevey, David
Abstract: Objective: Leventhal's common sense model of self‐regulation highlights how specific beliefs about illness influence psychological outcomes. Little is known on how such beliefs relate to BRCA1/2 adjustment. Furthermore, beliefs about one's self‐concept may be relevant to genetic conditions and may relate to psychological wellbeing. Methods: One‐hundred and eighteen female BRCA1/2 carriers from an Irish University Hospital completed questionnaires for this cross‐sectional study. Outcomes measured were state anxiety and physical and mental health‐related quality of life (HRQOL). Explanatory variables included sociodemographics, health anxiety, illness perceptions, coping and self‐concept . Hierarchical multiple regression analyses were conducted. Results: Then, 44% of participants had clinically significant state anxiety and 12% had clinically significant health anxiety. Vulnerability, stigma, mastery and health anxiety explained 42% of the variance in state anxiety. Previous mental health difficulty, vulnerability, stigma, mastery and health anxiety explained 40% of the variance in mental HRQOL. Dysfunctional coping strategies were strongly related to the physical functioning aspect of quality of life. Conclusion: BRCA‐specific beliefs related to self and health anxiety are important factors to consider in the adjustment to BRCA1/2 confirmation.